Regulation of Partial and Reversible Endothelial-to-Mesenchymal Transition in Angiogenesis - Fang, Jennifer S.; Hultgren, Nan W.; Hughes, Christopher C. W. (Frontiers in Cell and Developmental Biology, 2021)
During development and in several diseases, endothelial cells (EC) can undergo complete endothelial-to-mesenchymal transition (EndoMT, or EndMT) to generate endothelial-derived mesenchymal cells. Emerging evidence suggests that ECs can also undergo a partial EndoMT to generate cells with intermediate endothelial- and mesenchymal-character. This partial EndoMT event is transient, reversible, and supports both developmental and pathological angiogenesis. Here, we discuss possible regulatory mechanisms that may control the EndoMT program to dictate whether cells undergo complete or partial mesenchymal transition, and we further consider how these pathways might be targeted therapeutically in cancer.